Improve antenna performances by DGS techniques: article / Rosmawati Shafie - Shafie, Rosmawati
This paper presents the design of microstrip circular patch antenna with Defected Ground Structure (DGS) for wireless communication. The proposed antenna has been simulated at 2.45 GHz frequency using Computer Simulation Tool (CST) Design Environment software. The substrate using Frame Retardant 4 (FR-4) with εr = 4.7 and thickness 0.8mm. Copper with thickness 0.035mm is used as a patch and ground. DGS with various sizes and shapes is build below the circular patch. The resultant antenna with DGS and without DGS was analyzed in term of return loss, bandwidth, gain, Voltage Standing Wave Ratio (VSWR), and radiation pattern. The fabricated antenna was then to be measured by Vector Network Analyzer (VNA) to carry out its S11 and VSWR result. The result from simulation and measurement will be compared.